The Effect of Tax Awarness, Tax Sanctions, Quality of Tax Services, and Level of Education on Taxpayer's Motivation to Fulfill its Obligations - Erling, Gorajodi; Hasanah, Nuramalia; Muliasari, Indah (LPPM Universitas Negeri Jakarta, 2022)
This purpose of this research is to know the effect of taxpayers awareness, tax sanctions, tax service quality, and education level to the motivation of personal taxpayers in fulfilling tax obligations. The sample of this research came from of 100 correspondences who are all registered as individual taxpayers in Pasar Rebo Tax Office. Sampling using accidental sampling with a significance level uses is 0.05. Based on the results of the study shows that taxpayers awareness has a positive effect on the motivation of personal taxpayers in fulfilling tax obligations, tax santions has a positive effect on the motivation of personal taxpayers in fulfiling tax obligations, tax service quality has a positive effect on the motivation of personal taxpayers in fulfilling tax oblogations, and education level effect on the motivation of personal taxpayers in fulfilling tax obligations.